Gebze’de Şehirsel Büyümenin Mekansal-Zamansal Analizi - Mehmet Fatih Döker; Müjde Aydoğdu (Coğrafi Bilimler Dergisi, 2019)
The main determinant dynamics of cities are economic and social processes. The main element of these processes is the demographic characteristic of the population. Due to its geographic location and conditions, the city of Gebze has been convenient and populated for human activities from past to present. Gebze, which has been an important settlement since the early years of the republic, continued to exist as a quiet town until the 1960s. Then the urbanization process has been accelerated depending on industrial activities in the city. The industrial policies implemented after the year of 1970 caused the development of industrial function of the city and the increase of population in the city. The first organized industrial region (OIR) became operational in 1990 due to increasing transportation investments, which has made Gebze a truly industrial city. In this study, land cover change of the city since the year of 1990 has been analyzed. An important basis for smart city growth models was created by focusing on the direction and development of land cover change.